ON THE CONCEPT OF ECONOMIA CIVILE AND "FELICITAS PUBLICA": A COMMENT ON FEDERICO D'ONOFRIO. Issue 2 (9th April 2017) - Bruni, Luigino
Abstract : In "On the Concept of 'Felicitas Publica' in Eighteenth-Century Political Economy, " a recent paper in this journal, Federico D'Onofrio strongly criticizes the interpretation that Luigino Bruni and Stefano Zamagni have offered of the eighteenth-century Neapolitan tradition of civil economy and public happiness, as articulated by Antonio Genovesi. D'Onofrio claims that Bruni and colleagues have not fully explored the political meaning of public happiness within eighteenth-century economics, and that Bruni unfairly criticized methodological individualism on the basis of the intrinsically social character of happiness. This paper is a reply to D'Onofrio.